ANALISIS NILAI PENDIDIKAN ISLAM PADA ERA GLOBAL MENURUT HAMKA - Abdul Rozak (LPPM Sekolah Tinggi Agama Islamm (STAI) Fatahillah Serpong, Tangerang Selatan-Banten, Indonesia, 2022)
The purpose of this study is to analyze the values ​​of Islamic education in the era of globalization from the perspective of Buya Hamka. In this study using a type of qualitative research is research that is capable of producing descriptive data. The research method used is literature review. Source of data used in this research is secondary data. The procedure carried out in this study using the literature review method was to collect library materials sourced from journals and books. The data analysis technique used is content analysis. The components of Islamic education according to Hamka include teaching materials and methods, educators, students and educational assessments that are more relevant to Islamic education in the era of globalization